Factores de éxito en el emprendimiento femenino turístico rural en Costa Rica - Gabaldón, Patricia; Gutiérrez Cruz, Merlyn; Such Devesa, María Jesús (Universidad de Alicante, 2021)
This research article aims to define the profile of Costa Rican women entrepreneurs in the rural tourism sector and to determine whether their characteristics and those of their ventures are related to their performance. A mixed methodology has been adopted based on semi-structured and in-depth interviews. The results highlight the importance of family support and contact networks as essential elements for the development of successful enterprises. Family and networks provide two essential elements for the success of women entrepreneurs: access to finance and the formalization of their business. It is particularly important to point out the contribution of this research to the under-studied field of rural entrepreneurs, given their contributions to reducing poverty for which access to information has traditionally been very limited.
Keywords: Performance; Rural women entrepreneurs; Tourism; Costa Ricans; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 1 - Fin de la pobreza; ODS 9 - Industria, innovación e infraestructura; ODS 5 - Igualdad de género